A review of financial instruments to pay for predator conservation and encourage human-carnivore coexistence. - Dickman, A; Macdonald, E; Macdonald, D (2011)
One of the greatest challenges in biodiversity conservation today is how to facilitate protection of species that are highly valued at a global scale but have little or even negative value at a local scale. Imperiled species such as large predators can impose significant economic costs at a local level, often in poverty-stricken rural areas where households are least able to tolerate such costs, and impede efforts of local people, especially traditional pastoralists, to escape from poverty. Furthermore, the costs and benefits involved in predator conservation often include diverse dimensions, which are hard to quantify and nearly impossible to reconcile with one another. The best chance of effective conservation relies upon translating the global value of carnivores into tangible local benefits large enough to drive conservation "on the ground." Although human-carnivore coexistence involves significant noneconomic values, providing financial incentives to those affected negatively by carnivore presence is a common strategy for encouraging such coexistence, and this can also have important benefits in terms of reducing poverty. Here, we provide a critical overview of such financial instruments, which we term "payments to encourage coexistence"; assess the pitfalls and potentials of these methods, particularly compensation and insurance, revenue-sharing, and conservation payments; and discuss how existing strategies of payment to encourage coexistence could be combined to facilitate carnivore conservation and alleviate local poverty.